006 Quality improvement: management of myotonic dystrophy patients in tertiary care centres. Issue 12 (14th November 2019) - Odunsi, Sola; Roberts, Mark; Lilleker, James; Bentley, Andrew; Felton, Tim
Abstract : Background: Myotonic Dystrophy type 1 is an inherited multisystem disorder with a European prevalence of 3–15 per 100, 000. Cardiorespiratory complications (e.g. arrythmia, respiratory failure) account for around 70% of early deaths. In many cases this could be prevented though periodic screening and timely intervention, including with pacemakers or non-invasive ventilation, where indicated. Recently, international consensus-based care recommendations have been published with a view to reduce mortality by improving quality and standardising care for patients with Myotonic Dystophy type 1. We hypothesised that nationally, adherence to these recommendations is likely to be poor. Methods: We audited the care of patients with Myotonic Dystrophy type 1 at the Manchester Centre for Clinical Neuroscience (MCCN) and the University Hospital South Manchester (UHSM) Ventilation Clinic against consensus-based care recommendations. A data collection proforma was created based on the recent care recommendations. Retrospective case note review was performed. Results and conclusion: Data collection and analysis is ongoing. Full results will be presented at the conference along with a quality improvement action plan. These results will also feed in to a planned redevelopment of tertiary neuromuscular services in the region.